Towards reliable three-electrode cells for lithium–sulfur batteries. Issue 5 (20th December 2021) - Chien, Yu-Chuan; Brandell, Daniel; Lacey, Matthew J.
Abstract : A simple three-electrode cell format for lithium–sulfur batteries is proposed to enable the deconvolution of the positive and negative electrode potentials from the cell voltage and therefore the measurement of their individual resistances. Abstract : Three-electrode measurements are valuable to the understanding of the electrochemical processes in a battery system. However, their application in lithium–sulfur chemistry is difficult due to the complexity of the system and thus rarely reported. Here, we present a simple three-electrode cell format with relatively good life time and minimum interference with the cell operation.